Penerapan Pendidikan Keselamatan di Sekolah Dasar - Sabariah; Erni Srihastuti (Jurnal Pendidikan Dasar Islam, 2023)
The purpose of this research is to describe the application of safety education in basic education. This research method uses descriptive qualitative. This data source uses primary sources, namely from book literature, journal studies, magazines, or websites that support research. This data analysis uses descriptive analysis. The results of this study indicate that athletics in Indonesia is defined as a sport that competes in street, running numbers. The benefits of health and safety education in general are to change individual or community behavior in the health sector.